2021
DOI: 10.1101/2021.09.14.460270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exocytosis of the silicified cell wall of diatoms involves extensive membrane disintegration

Abstract: Diatoms are unicellular algae that are characterized by their silica cell walls. The silica elements form intracellularly in a membrane-bound organelle, and are exocytosed after completion. How diatoms maintain membrane homeostasis during the exocytosis of these large and rigid silica elements is a long-standing enigma. We studied membrane dynamics during cell wall formation and exocytosis in the diatom Stephanopyxis turris, using live-cell confocal microscopy and advanced electron microscopy. Our results prov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Recently, De Hann et al used live-cell confocal microscopy and advanced electron microscopy to observe the frustule assembly process for the rst time and con rmed that the frustule forms inside a membrane-bound compartment (Silica Deposition Vesicle, SDV) called the silicalemma. The authors also found that the silicalemma tightly surrounds the forming frustule during the whole silici cation process, suggesting an essential role of the silicalemma in frustule morphology [32]. Based on previous observations that the cytoskeleton plays an important role in shaping frustule, it can be speculated that silicalemma-spanning proteins mediate the interaction between the SDV and cytoskeleton [28, 29,33].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Recently, De Hann et al used live-cell confocal microscopy and advanced electron microscopy to observe the frustule assembly process for the rst time and con rmed that the frustule forms inside a membrane-bound compartment (Silica Deposition Vesicle, SDV) called the silicalemma. The authors also found that the silicalemma tightly surrounds the forming frustule during the whole silici cation process, suggesting an essential role of the silicalemma in frustule morphology [32]. Based on previous observations that the cytoskeleton plays an important role in shaping frustule, it can be speculated that silicalemma-spanning proteins mediate the interaction between the SDV and cytoskeleton [28, 29,33].…”
Section: Introductionmentioning
confidence: 94%
“…(2) only the proximal silicalemma SAPs were observed to interact with microtubules, whereas the distal silicalemma SAPs may interact with other cellular components or the original plasma membrane. De Hann et al discovered that the distal silicalemma is in very close proximity to the original plasma membrane, with a spacing distance of only 20 nm [32]. Such a con ned space is too narrow for microtubules to t into.…”
Section: Mechanism Of Frustule Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations